Life sentence : the brief and tragic career of Baltimore's deadliest gang leader - Bowden, Mark, 1951- (Atlantic Monthly Press, 2023)
"In this unprecedented deep dive into inner-city gang life, Mark Bowden takes readers inside a Baltimore gang, offers an in-depth portrait of its notorious leader, and chronicles the 2016 FBI investigation that landed eight of its members in prison. Sandtown is one of the deadliest neighborhoods in the world; it earned Baltimore its nickname "Bodymore, Murderland," and was made notorious by David Simon's classic HBO series The Wire. Drug deals dominate street corners, and ruthless, casual violence abounds. Montana Barronette grew up in the center of it all. He was the leader of the gang "Trained to Go," or TTG, and when he was finally arrested and sentenced to life in prison, he had been labeled "Baltimore's Number One Trigger Puller." Under Tana's reign, TTG dominated Sandtown. After a string of murders are linked to TTG, each with dozens of witnesses too intimidated to testify, three detectives set out to put Tana in prison for life. For them, this was never about drugs: it was about serial murder. An acclaimed journalist who spent his youth in the white suburbs of Baltimore, Mark Bowden returns to the city with exclusive access to key FBI files and unprecedented insight into one of the city's deadliest gangs and its notorious leader. As he traces the rise and fall of TTG, Bowden uses wiretapped drug buys, police interviews, undercover videos, text messages, social media posts, trial transcripts, and his own ongoing conversations with Tana's family and community to create the most in-depth account of an inner-city gang ever written. With his signature precision and propulsive narrative, Mark Bowden positions Tana--as a boy, a gang leader, a killer, and now a prisoner--in the context of Baltimore and America, illuminating his path for what it really was: a life sentence"--